The Development Strategy of Waqf Insurance Benefits and Investment Benefits in Islamic Life Insurance PT. Takaful Medan Branch - Chuzaimah Batubara; Lilis Pujiyanti; Rahmi Syahriza (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to evaluate the strategy of developing waqf benefits in Sharia insurance and investment benefits in Sharia life insurance at PT Takaful Keluarga Medan, and to formulate strategic recommendations based on SWOT and QSPM analysis. The research method used is descriptive qualitative by applying SWOT and QSPM analysis. The results of the SWOT analysis show that the strategic position of PT Takaful Keluarga Medan is in quadrant 1 (positive strategy), between strengths and opportunities. Strategic recommendations include consistent development of Sharia products, increasing public trust through excellent service, platform diversification for better accessibility, training and socialization about waqf benefits, and improving the quality of human resources. QSPM analysis indicates that the prioritized development strategy is to leverage the Sharia insurance brand and enhance customer trust through digital platforms, increase the number of marketers, improve product quality, workforce understanding, and collaboration with Islamic institutions. The researchers hope that these findings can serve as considerations for students in selecting alternative strategies, while for future researchers, it is hoped that they can analyze other factors and variables not explored in this study.